2012
DOI: 10.1111/j.1525-1470.2012.01730.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Pemphigus Vulgaris: Durable Treatment Responses Achieved with Prednisone and Mycophenolate Mofetil (MMF)

Abstract: Pemphigus vulgaris (PV) is a chronic autoimmune blistering disease of the skin and mucous membranes. Most cases occur in adults; cases in children are rare. This report describes the clinical presentations and treatment responses of three children with PV, as confirmed according to histology and indirect immunofluorescence studies. In all three cases, oral prednisone used in conjunction with mycophenolate mofetil (MMF) resulted in complete clinical remission, during which all pharmacotherapy was successfully d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 19 publications
(66 reference statements)
0
25
0
3
Order By: Relevance
“…There is no epidemiologic research on the incidence of pediatric pemphigus; however, it is suggested that 1.4%‐2.9% of all PV cases are pediatric cases . It affects both sexes equally, and the mean age of onset is 12 years . Pediatric pemphigus affected approximately 3% in two case series of pemphigus in Turkey .…”
Section: Introductionmentioning
confidence: 99%
“…There is no epidemiologic research on the incidence of pediatric pemphigus; however, it is suggested that 1.4%‐2.9% of all PV cases are pediatric cases . It affects both sexes equally, and the mean age of onset is 12 years . Pediatric pemphigus affected approximately 3% in two case series of pemphigus in Turkey .…”
Section: Introductionmentioning
confidence: 99%
“…Only 46 cases of childhood PV (onset age range, 1.5-12 years), including the present case, have been reported in the literature. Mycophenolate mofetil has been used successfully by Baratta et al 6 , obtaining durable remission. It should be started at a low dosage (500 mg/day), and then increased gradually.…”
Section: Dear Editormentioning
confidence: 99%
“…In conclusion, based on our and Terashita's observations, 1 and other recent studies. 6,8 Mycophenolate mofetil can be considered as an appropriate treatment option for pediatric patients with BD, PV, and a range of autoimmune diseases.…”
Section: Dear Editormentioning
confidence: 99%
“…Los más utilizados en pediatría son la azatioprina (2-4 mg/kg/día, hasta 100-300 mg al día) 7 y el mofetilmicofenolato (2-3 g/día). 5,8 Otras drogas descritas son la ciclofosfamida por vía oral (1-3 mg/kg/día), la ciclosporina (5 mg/kg/día), la dapsona (1,5 mg/kg/día) y el metotrexate (10-20 mg/semana). 4,5,7 Para los casos de pénfigo grave que no responden a la combinación de corticoides e inmunosupresores, está descrito el uso de plasmaféresis o IgG endovenosa.…”
Section: Figura 3 Ampollas Con Contenido Seroso Erosiones Y Costrasunclassified